Extrusion 3D printing of intrinsically fluorescent thermoplastic polyimide: revealing an undisclosed potential - Kothavade, Premkumar; Kafi, Abdullah; Dekiwadia, Chaitali; Kumar, Viksit; Sukumaran, Santhosh Babu; Shanmuganathan, Kadhiravan; Bateman, Stuart (POLYMERS, 2024)
Keywords: Additive manufacturing; functional extrusion; high-performance polymers; thermoplastic polyimide

Design, fabrication and comprehensive testing of biodegradable 3D printable hybrid polymer airway splints - Naik, Sonali S.; Vongsvivut, Jitraporn; Dekiwadia, Chaitali; Abraham, Amanda N.; Dutta, Naba K.; Choudhury, Namita Roy; Nair, Kiran Sukumaran (Journal of Materials Chemistry B, 2025)
The trachea plays a critical role in respiration and airway protection but is susceptible to damage from pathological conditions such as stenosis, fistula, obstruction, and malacia. While existing treatment options are useful, they often have limitations, driving the need for innovative alternatives. This study introduces a novel approach using 3D printing technology to create hybrid degradable tracheal splints made of pectin-g-polycaprolactone (pec-g-PCL). We synthesized and characterized various compositions of pec-g-PCL to assess their physicochemical properties and tested their suitability for 3D printing. The resulting materials demonstrated the potential for use as tracheal splints. Using CAD software, we created two distinct designs, which were then fabricated according to those specifications. Micro-computed tomography (micro-CT) imaging revealed splint porosities ranging from 80% to 90%, highlighting their intricate internal microarchitecture. Design verification was conducted through numerical simulations, based on finite element modeling (FEM), to evaluate mechanical properties and computational fluid dynamics (CFD) for assessing the airflow dynamics of the fabricated tracheal splints. Degradation studies indicated that the 3D-printed scaffolds exhibited approximately 30% degradation over a period of 35 days. In vitro, biocompatibility assessments confirmed the scaffold's compatibility with biological systems. These findings demonstrate the potential of pec-g-PCL-based tracheal splints as a promising solution to overcome limitations in current treatments. This research paves the way for advanced biomaterials that could revolutionize patient care by offering more effective solutions for managing tracheal disorders.